Impact of the new fast track kidney allocation scheme for declined kidneys in the United Kingdom. (28th September 2015) - White, Alan D.; Roberts, Heather; Ecuyer, Clare; Brady, Kathryn; Pathak, Samir; Clark, Brendan; Hostert, Lutz H.; Attia, Magdy S.; Wellberry‐Smith, Matthew; Hudson, Alex; Ahmad, Niaz
Abstract: Introduction: A "new" fast track kidney allocation scheme (FTKAS) was implemented in the UK in 2012 for offering of previously declined kidneys. We evaluated the impact of the FTKAS in utilization of declined kidneys and outcome. Methods: Adult renal transplant centers were surveyed. Overall utilization was evaluated using National Health Service Blood and Transplant (NHSBT) data. Outcome of FTKAS kidneys in our center was analyzed. Results: Centers cited graft, patient outcome concerns, and inadequate logistical support for their non‐FTKAS participation. In the first year of the scheme, 266 kidneys were offered through the FTKAS, 158 were transplanted in 10 centers (59%). In comparison, 166 kidneys were offered through previous system over five yr (2006–2011), and 65 were utilized in 59 transplants (39%). In our center, 42 kidneys were transplanted in 39 recipients. One‐yr graft and patient survival were both 95%. Results were comparable to a matched group of kidney transplants during the same periods allocated via the standard scheme. Conclusions: The FTKAS has led to effective utilization of the declined kidneys with outcome comparable to kidneys allocated through the standard scheme. Non‐participation based on outcome concerns is mostly subjective while logistical issues need to be addressed.